The values of low-density lipoprotein cholesterol and acute coronary syndrome. (11th May 2021) - Ferraz, LM; Faustino, A; Neves, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: All individuals with a history of acute coronary syndrome (ACS) should receive intensive statin therapy in order to achieve the desirable low-density lipoprotein cholesterol (LDL-C) values recently modified in the guidelines of the European Society of Cardiology. Purpose: To evaluate the lipid profile control of ACS patients with 6 year follow-up. Methods: Retrospective study of 138 consecutive patients (P) admitted in our hospital for ACS during one year: 63 ± 13 years, 76.8% male, 26.9% with history of coronary artery disease and 56.5% of dyslipidemia. A 6 year follow-up was performed and a therapeutic goal was defined as LDL-C values below 55mg/dL and an LDL-C reduction of ≥50% from baseline, according to the guidelines of the European Society of Cardiology. High/moderate/low intensity statins were defined according to the therapeutic recommendations of the American College of Cardiology. Univariate analysis was performed. Results: The mean LDL-C value at ACS admission was 112.5 ± 36.9mg/dL. 96.4% of patients were discharged on statins: 41.3% with rosuvastatin 10mg, 15.2% with simvastatin 20mg, 15.2% with atorvastatin 10mg, 10.9% with pitavastatin 2mg and 6.5% with atorvastatin 20mg. Antidislipidemic therapy was changed in 7.9% of patients in the scheduled evaluation 1 month after discharge. The mean LDL-C value after a 6 year follow-up was 83.6 ± 27.2mg/dL, with 85.8% P not meeting the defined therapeutic goal. Most of them (97.5%) continued medicated with statin, however, only 28.3% of P were on high-intensity statins and 3.8% were on low-intensity statins, despite the verified statistically significant association between LDL-C values and statin type used (high/medium/low intensity, p < 0.05). Conclusion: Despite the proven benefit of statins, especially in high-risk patients, there are still aspects to improve, notably in the establishment of more effective therapies in order to achieve the desired new goals.